Climatological assessment of water harvesting technology through dug-out ponds in arid regions - SURYANARAYANA, G; MEGERI, SN (MAUSAM, 1987)
The daily rainfall data of Bijapur for the period from 1930 to 1981 is studied to assess the feasibility of water harvesting through dug -out ponds. The initial and conditional probability analysis is done for receiving rainfall amounts of 10 to 30 mm per week to understand the continuity of wet spells. Daily soil water balance of deep black soils of Bijapur is studied to work out the availability of excess water for runoff collection. The study brings out the importance of thorough understanding of rainfall behaviour of arid regions- while developing water harvesting technology.